Equilibrium Studies of the magnetic surfaces function  of Tokamak system with poloidal divertor - Alhasi, Awad (Libyan Journal of Science &Technology, 2022)
An analytical solution for the magnetic field B produced by current filaments and the related magnetic surface function are given. The use of as a coordinate in this system is explored, and its hyperbolic form is given. The simple character of the plasma drift velocity for this coordinate is derived.